An improved approach for H∞ design of linear quadratic tracking control for chemical processes with partial actuator failure. (October 2017) - Zhang, Ridong; Gao, Furong; Christofides, Panagiotis D.
Highlights: Improved design of LQ design using expanded state space model is derived. The design is verified on an injection velocity control issue. Robustness criterion against model/plant mismatch is further proposed. Abstract: For chemical processes under partial actuator failure, a new H∞ design of linear quadratic (LQ) tracking control approach is proposed for robust tracking of set-point against actuator faults and unknown disturbance. In view of the disadvantages of traditional H∞ control that only take into account the output tracking error or the corresponding converted state variables into the controller design, a new state space model in which the process state variables and tracking error are combined and can be regulated separately is proposed first. Based on this model development, a new H∞ control strategy is proposed to yield improved tracking performance and disturbance rejection. The system performance robustness criterion against model/plant mismatch is further proposed to guarantee monotonicity conditions, which are sufficient for robust system stability. The case study on an injection velocity control further demonstrates the merits and effectiveness of the proposed method.